Portal Vein Tumor Thrombosis and Hepatocellular Carcinoma – The Changing Tides - Khan AR; Wei X; Xu X (Journal of Hepatocellular Carcinoma, 2021)
Abdul Rehman Khan,1– 3 Xuyong Wei,1,3,4 Xiao Xu1– 4 1Department of Hepatobiliary and Pancreatic Surgery, The Center for Integrated Oncology and Precision Medicine, Affiliated Hangzhou First People’s Hospital, Zhejiang University School of Medicine, Hangzhou, 310006, People’s Republic of China; 2Department of Hepatobiliary and Pancreatic Surgery, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, 310003, People’s Republic of China; 3NHC Key Laboratory of Combined Multi-organ Transplantation, Hangzhou, 310003, People’s Republic of China; 4Institute of Organ Transplantation, Zhejiang University, Hangzhou, 310003, People’s Republic of ChinaCorrespondence: Xiao XuDepartment of Hepatobiliary and Pancreatic Surgery, The Center for Integrated Oncology and Precision Medicine, Affiliated Hangzhou First People’s Hospital, Zhejiang University School of Medicine, Hangzhou, 310006, People’s Republic of ChinaEmail zjxu@zju.edu.cnAbstract: Portal vein involvement is considered one of the most fearful complications of hepatocellular carcinoma (HCC). Portal vein tumor thrombosis (PVTT) is associated with aggressive tumor biology (high grade), high tumor burden (number and size of lesions), high levels of serum markers (AFP), poor liver function (deranged LFT), and poor performance status of patients. The Barcelona Clinic Liver Cancer staging system places HCC patients with PVTT in advanced stage (BCLC Stage-C). This group contains a fairly heterogeneous patient population, previously considered candidates for palliative systemic therapy with sorafenib. However, this provided modest overall survival (OS) benefit. The results of a recent Phase III (IMbrave150) trial favor the combination of atezolizumab and bevacizumab over sorafenib as a standard of care in advanced unresectable HCC. While only lenvatinib proved to be non-inferior against sorafenib in a phase III (REFLECT trial), regorafenib (RESORCE trial), ramucirumab (REACH-2), and cabozantinib (CELESTIAL) have been approved second-line therapy in phase III clinical trials. Recently, the data on the prospect of other modalities in the management of HCC with PVTT is mounting with favorable results. Targeting multiple pathways in the HCC cascade using a combination of drugs and other modalities such as RT, TACE, TARE, and HAIC appear effective for systemic and loco-regional control. The quest for the ideal combination therapy and the sequence set is still widely unanswered and prospective trials are lacking. With the armament of available therapeutic options and the advances and refinements in the delivery system, down-staging patients to make them eligible for curative resection has been reported. In a rapidly evolving treatment landscape, performing surgery when appropriate, in the form of LR and even LT to achieve cure does not seem farfetched. Likewise, adjuvant therapy and prompt management of the recurrences holds the key to prolong OS and DFS. This review discusses the management options of HCC patients with PVTT.Keywords: hepatocellular carcinoma, portal vein tumor thrombosis, systemic therapy, transarterial chemoembolization, hepatic artery infusion chemotherapy, radiotherapy, multimodality treatment, liver resection, liver transplantation